Thermal cycling stability of fly ash based geopolymer mortars. (15th November 2017) - Colangelo, F.; Cioffi, R.; Roviello, G.; Capasso, I.; Caputo, D.; Aprea, P.; Liguori, B.; Ferone, C.
Abstract: In this paper fly ash based geopolymer mortars have been prepared and their thermal behavior evaluated in order to assess the suitability of fly ash based alkali-activated binders for thermal energy storage in solar thermal plants. Different parameters, such as binder/aggregate ratio, percentage of fly ash replaced by slag, temperature and curing time, have been changed and optimized using the Design Of Experiments (DOE) approach. In order to estimate the thermal cycling stability of geopolymeric mortars at elevated temperatures, mechanical strength and weight loss of each sample subjected to different thermal cycles in the temperature range 150–550 °C were evaluated. Finally, thermal conductivity of some of the mixtures, selected on basis of the thermal stability test results, have been measured. Fly ash based geopolymeric mortars remained stable after each thermal treatment and specimens treated at elevated temperatures retained acceptable compressive strength. The thermal stability was preserved also after repeated thermal cycles, proving that fly ash based geopolymers are suitable materials for thermal energy storage concretes. Graphical abstract: Highlights: Fly ash based geopolymer mortars were proposed for thermal energy storage application. Geopolymerization process parameters were optimized using DOE approach. The thermal stability of the mortars was evaluated after repeated thermal cycles. Fly ash based geopolymer mortars showed good thermal stability at elevated temperatures.